COMPARATIVE ANALYSIS OF THE WELFARE LEVEL OF WOMEN FARMERS IN THE GAYO WOMEN'S COFFEE COOPERATIVE WITH THE ARA CAHAYANI GAYO COOPERATIVE IN BENER MERIAH DISTRICT - Erika safira; Emmia Tambarta Kembaren; Hafni Zahara (LPPM Universitas Malikussaleh - Indonesia, 2024)
There are several coffee cooperatives in Bener Meriah Regency including Gayo Women's Coffee Cooperative and Ara Cahayani Gayo Cooperative that both improve the welfare of farmers, but it is not yet known which cooperative provides a higher level of welfare for women farmers. The research was conducted at Gayo Women's Coffee Cooperative and Ara Cahayani Gayo Cooperative in Bener Meriah Regency. This study aims to analyze the comparison of the welfare level of women farmers in Gayo Women's Coffee Cooperative and Ara Cahayani Gayo Cooperative in Bener Meriah Regency. The data analysis method used is qualitative and quantitative analysis. The results showed that from the scoring results, a higher level of welfare was felt by female farmers in the Gayo Women's Coffee Cooperative as many as 32 people or 82% and the remaining 7 people or 18% of female farmers were in the medium welfare level category. Meanwhile, female farmers in Ara Cahayani Gayo Cooperative who feel high welfare as many as 17 people or 45% and others as many as 21 people or 55% are at a moderate level of welfare. Then based on the results of the t test (independent t test) obtained a sig value of 0.000 <0.05, meaning that there is a significant difference in the level of welfare of female farmers in the Gayo Women's Coffee Cooperative with Ara Cahayani Gayo Cooperative. Keywords: Comparative, Cooperative, Welfare, Women Farmers.